Ladders - Vegetius Renatus, Flavius (Vier Bücher der Ritterschafft, 1529)
The image shows a soldier climbing a siege ladder alongside a schematic of a different ladder in three parts that can be screwed together.
Keywords: Ladders; Military art and science; Siege warfare